DIGITALISASI EKSPOR SEBAGAI STRATEGI INKLUSIF BAGI UMKM DI KABUPATEN ENDE, NUSA TENGGARA TIMUR: STUDI LITERATUR PADA PENGEMBANGAN EKSPOR KAIN TENUN IKAT ENDE-LIO - Devrianti Rahma Satria; Fransiska Clarita Saputri Rani; Tri Eko Darmawan; Nalazah Muzzaila Esta; Ibra Amazil; Arga Christian Sitohang (widya balina, 2025)
. In the era of digitalization and globalization, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face both opportunities and challenges in international trade. This study aims to analyze export digitalization as an inclusive strategy for MSMEs producing Ende-Lio Ikat Weaving in Ende Regency, East Nusa Tenggara (NTT), to increase global market access and preserve local cultural values. The research method used is descriptive qualitative with a literature study approach to analyze the factors that influence the adoption of export digitalization. The results show that digital platforms enable MSMEs to increase product visibility, integrate cultural values in international trade, and reach global consumers. Key challenges include infrastructure limitations, low digital literacy, and export product readiness. Inclusive strategies that combine technology, training, institutional support, and compliance with international standards are essential to empower artisans in remote areas. These findings serve as a reference for policy development to support the sustainable participation of culture-based MSMEs.